ISU-ISU DINAR DAN DIRHAM - Fatma Khalieda (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
Lately there dinars are very active in Malaysia. They argue that if this return is achieved, all modern economic diseases such as inflation, credit, and unemployment will be resolved. M. Syafii Antonio says the current banknote system opens the door to fraudulent acts carried by financial institutions on Wall Street. That we should go back to the golden system where the currency is made of gold and tighten the monitoring system and urge Muslim countries to return to the "Gold Dinar" as a single currency. in this journal discusses the dinar and dirham, its use from time to time, as well as the reasons put forward by some economists against the use of dinar and dirham agreement. conclude that nothing wrong in the use of fiat money as long as it is closely monitored by the government. Because Rasulullah also never justify to keep using the dinar and dirham as currency. Because the use of dinar and dirham does not guarantee will not be inflation.